A systematic review of the association between lower urinary tract symptoms and falls, injuries, and fractures in community-dwelling older men. (2nd July 2016) - Noguchi, Naomi; Chan, Lewis; Cumming, Robert G.; Blyth, Fiona M.; Naganathan, Vasi
Abstract: Background : Lower urinary tract symptoms (LUTS) have been associated with falls in studies either exclusively or predominantly of women. It is, therefore, less clear if LUTS are risk factors for falls in men. Methods : We conducted a systematic review of the literature on the association between LUTS and falls, injuries, and fractures in community-dwelling older men. Medline, Embase, and Cinahl were searched for any type of observational study that has been published in a peer-reviewed journal in English language. Studies were excluded if they did not report male-specific data or targeted specific patient populations. Results were summarized qualitatively. Results : Three prospective cohort studies and six cross-sectional studies were identified. Incontinence, urgency, nocturia, and frequency were consistently shown to have weak to moderate association with falls (the point estimates of odds ratio and relative risk ranged from 1.31 to 1.67) in studies with low risk of bias for confounding. Only frequency was shown to be associated with fractures. Conclusions : Urinary incontinence and lower urinary tract storage symptoms are associated with falls in community-dwelling older men. The circumstances of falls in men with LUTS need to be investigated to generate hypotheses about what types of interventions may be effective in reducing falls.